Septins and flaviviral proteases: a structural analysis - Rosa, Higor Vinícius Dias (2022)
In 2016, a 26-fold increase in microcephaly cases during a Zika virus outbreak alarmed the country. In these cases, during infection, the virus has as its main target the neuronal progenitor cells (NPCs), decreasing their proliferation leading to cell death, which contributes to microcephaly. By identifying the isolated effect of viral proteins on these cells, Li et al. (2019) observed that the NS2B-NS3 protease is able to mediate virus neurotoxicity, through the cleavage of host proteins essential to neurogenesis (especially septins). There was a reduction in the levels of these proteins after overexpression of the protease, confirming them as a target. In the same study, the cytotoxic effects were related to the cleavage of the C- terminal domain of septin 2, rescuing cytokinesis after the expression of septin 2 \"resistant\" to the cleavage. Although the cellular effects (after cleavage) were determined, the immediate effect and the importance of the cleaved region in the formation of septin structures was still unclear. It was also unknown whether the septin cleavage was specific for Zika or whether other flavivirus proteases could cleave them. In this work, truncated septin constructions were used to assemble heterocomplexes in order to characterize them and evaluate their potential to polymerize. Proteolytic activity assays and interaction analyses involving septins, and different flavivirus proteases were also performed. Based on these studies, it was found that hexameric complexes are still able to be formed even in the absence of the C-terminal domains, despite influencing stability. However, when analysing the capacity to form filaments, it can be seen that the absence of these domains influences not only the morphology of the filaments formed but also the concentration required for the appearance of these high-order structures. More specifically, the C-terminal domain of SEPT2 cleaved by ZIKV protease proved to be critical for observing filaments at physiological concentrations, thus justifying the subsequent effects caused by its cleavage. At the same time, a specificity for the ZIKV protease in septin cleavage was observed when compared to YFV. The explanations given for the greater efficiency of this off-target cleavage are the closer correspondence between the sequence of the cleavage region in SEPT2 and the preferred sequence for ZIKV cleavage when compared to YFV, and the greater intrinsic catalytic efficiency of the protease from ZIKV. On the latter point, we observe that the two proteases show differences in their oligomerization profiles in solution, which (allied to other factors) could have some influence on catalytic activity. Finally, from the analysis of the interaction of septins with inactive proteases, it can be verified that the cleavage occurs transiently, and a stable complex between these proteins cannot be obtained. A peptide representing the sequence of the SEPT2 cleavage region was synthesized, and preliminary co-crystallization assays were performed. A possible structure of this complex would be very interesting for understanding the cleavage process and for drug development against microcephaly. We hope that all these results will help understand the implications of septin-2 cleavage and its relationship to the microcephaly caused by Zika virus infection.